2021
DOI: 10.3892/mmr.2021.12575
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid inhibits osteoclastogenesis and bone resorptive function by suppressing RANKL‑mediated NF‑κB and JNK and their downstream signalling pathways

Abstract: Targeting excessive osteoclast differentiation and activity is considered a valid therapeutic approach for osteoporosis. Zoledronic acid (Zol) plays a pivotal role in regulating bone mineral density. However, the exact molecular mechanisms responsible for the inhibitory effects of Zol on receptor activator of nuclear factor (nF)-κB ligand (ranKl)-induced osteoclast formation are not entirely clear. The present study aimed to investigate the role of Zol in osteoclast differentiation and function, and to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…ZA can inhibit the fusion of osteoclast precursors and bone resorption activity of osteoclasts by suppressing RANKL/RANK-induced osteoclast-related genes ( Cheng et al, 2021 ; Lin et al, 2021 ; Huang et al, 2022 ). It has been demonstrated experimentally that ZA can strongly inhibit the formation of tartrate-resistant acid phosphatase (TRAP)+ multinucleated osteoclasts induced by RANKL/RANK pathway ( Cheng et al, 2021 ).…”
Section: Zoledronic Acid Inhibits Osteoclast Differentiationmentioning
confidence: 99%
See 3 more Smart Citations
“…ZA can inhibit the fusion of osteoclast precursors and bone resorption activity of osteoclasts by suppressing RANKL/RANK-induced osteoclast-related genes ( Cheng et al, 2021 ; Lin et al, 2021 ; Huang et al, 2022 ). It has been demonstrated experimentally that ZA can strongly inhibit the formation of tartrate-resistant acid phosphatase (TRAP)+ multinucleated osteoclasts induced by RANKL/RANK pathway ( Cheng et al, 2021 ).…”
Section: Zoledronic Acid Inhibits Osteoclast Differentiationmentioning
confidence: 99%
“…It has been demonstrated experimentally that ZA can strongly inhibit the formation of tartrate-resistant acid phosphatase (TRAP)+ multinucleated osteoclasts induced by RANKL/RANK pathway ( Cheng et al, 2021 ). An experimental study treated cells with ZA after 3 days of RANKL stimulation, and found that ZA significantly inhibited the mRNA expression levels of RANK, TRAP and calcitonin receptor in cells ( Huang et al, 2022 ), then the authors further analyzed the effect of ZA on osteoclast-specific markers, the results showed that RANKL stimulation significantly induced the expression of these osteoclast-specific markers, whereas ZA treatment significantly inhibited the expression levels of these markers.…”
Section: Zoledronic Acid Inhibits Osteoclast Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophage colony-stimulating factor (M-CSF) and the receptor activator of NF-κB ligand (RANKL) are important factors that induce the differentiation of osteoclast precursors into mature osteoclasts ( 4 ). A previous study evaluated regulation of various genes during osteoclastogenesis ( 5 ); however, the mechanism underlying osteoclast differentiation has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%